2015
DOI: 10.1016/j.chemosphere.2015.04.090
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of thiamethoxam on larvae of Africanized honey bee Apis mellifera (Hymenoptera: Apidae)

Abstract: Several investigations have revealed the toxic effects that neonicotinoids can have on Apis mellifera, while few studies have evaluated the impact of these insecticides can have on the larval stage of the honeybee. From the lethal concentration (LC50) of thiamethoxam for the larvae of the Africanized honeybee, we evaluated the sublethal effects of this insecticide on morphology of the brain. After determine the LC50 (14.34 ng/μL of diet) of thiamethoxam, larvae were exposed to a sublethal concentration of thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 48 publications
5
49
1
11
Order By: Relevance
“…It corroborates earlier findings about high toxicity of thiamethoxam on honey bee larvae (Tavares et al 2015). Tomé et al (2012) also reported adverse effects of neonicotinoid on stingless bees, showing significant reduction on survival rates of larvae of M. quadrifasciata anthidioides , when exposed to imidacloprid.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It corroborates earlier findings about high toxicity of thiamethoxam on honey bee larvae (Tavares et al 2015). Tomé et al (2012) also reported adverse effects of neonicotinoid on stingless bees, showing significant reduction on survival rates of larvae of M. quadrifasciata anthidioides , when exposed to imidacloprid.…”
Section: Discussionsupporting
confidence: 79%
“…At the highest doses (T2 and T3), our study revealed significant acceleration and delay in larval and pupal development times, respectively. In this context, Tavares et al (2015) showed that sublethal doses of thiamethoxam for honey bees can cause atypical progression of larval development stages. In addition, Wu et al (2011) reported delay in the development of A. mellifera workers exposed to pesticide residues, including neonicotinoids, and suggested that it could have negative consequences in the long term, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphogenetic field of the MBs is thus formed by concentric layers of proliferative cells. Knowledge of the development of the MBs and other honeybee brain regions such as the optic lobes (Marco Antônio and Hartfelder 2016) has broad scientific interest given that, for example, pesticides used in agriculture to control insects target the brains of larval bees (Tomé et al 2012;Tavares et al 2015). The ontogenetic saga of a social brain Using phalloidin and DAPI staining of wholemount brains, Moda et al (2013) showed clear peduncular organisation in worker larvae in the L5F phase.…”
Section: Honeybee Brain Development During the Larval Stagementioning
confidence: 99%
“…In Brazil, de Almeida Rossi et al (2013) reported that sublethal doses of imidacloprid induced negative effects on malpighian tubules of Africanized bees. Moreover, Brazilian researchers reported that thiamethoxam, also a neonicotinoid, was toxic for bee larva in lower doses which alter bee development (Tavares et al 2015).…”
Section: Agricultural Intensification and Use Of Pesticidesmentioning
confidence: 99%